Internal Structure and Magnetic Properties in Cobalt Ferrite Nanoparticles: Influence of the Synthesis Method. (18th March 2019) - Lavorato, Gabriel; Alzamora, Mariella; Contreras, Cynthia; Burlandy, Gabriel; Litterst, F. Jochen; Baggio‐Saitovitch, Elisa
Abstract: The design of novel nanostructured magnetic materials requires a good understanding of the variation in the magnetic properties due to different synthesis conditions. In this work, four different procedures for fabricating Co‐ferrite nanoparticles with similar sizes between 7 and 10 nm are compared by studying their structural and magnetic properties. Non‐aqueous methods based on the thermal decomposition of metal acetylacetonates at high temperatures, either with or without surfactants, provide highly crystalline nanoparticles with large saturation magnetization values and a coherent reversal of the magnetic moment. However, variations in the density of defects and in the shape of the nanocrystals determine the distribution of switching fields and the effective magnetic anisotropy, which reaches up to ≈1 × 10 7 erg cm −3 for oleic acid‐capped 9 nm nanoparticles. It is shown that the saturation magnetization values for nanoparticles produced by different methods are in the range between 49 and 95 emu g −1 due to differences in the stoichiometry, in the cation occupancy, in the magnetic disorder and in the spin canting of the magnetic sub‐lattices, the latter evaluated by in‐field Mössbauer spectroscopy. Abstract : A broad dispersion in the properties of magnetic nanoparticles is frequently observed, hindering the possibility to predict their efficiency in technological applications. Here, cobalt ferrite nanoparticles with similar size but remarkable variations in their magnetization and effective anisotropy are synthesized by four different methods. The influence of the structural coherence, defects and cation occupancy on the magnetic properties are discussed.